KORELASI ASUPAN ENERGI DAN AKTIFITAS FISIK TERHADAP OBESITAS SENTRAL - Lestari, Dwi; Efendi, Suradi; Nufus, Hayatun; Jannah, Miftahul (Ensiklopedia of Journal, 2025)
Abstract: Central obesity is a type of overweight characterized by the accumulation of fat in the central body area, especially around the abdominal cavity. The main cause of obesity is closely related to lifestyle, especially unhealthy diet and lack of physical activity. The purpose of this study was to determine the correlation of energy intake and physical activity with central obesity. The research design used in this study was cross sectional. The research was conducted in the Salo Health Center working area in July 2024. The population was all women aged 35-44 years in the Salo Health Center working area totaling 239 respondents. The sample amounted to 119 respondents. The sampling technique used cluster sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between energy intake (P value: 0.000) and no relationship between physical activity (P value: 0.137) on the incidence of central obesity. It is recommended for respondents to eat healthy food and do enough physical activity.Keywords: Physical Activity, Energy Intake, Central Obesity